Perbedaan Rata-Rata DMF-T Pada Masyarakat Yang Mengkonsumsi Air Minum Kemasan Isi Ulang Dan Air Sungai Yang Diendapkan - Naning K. Utami; Bainah Bainah; Muhammad Pahruddin (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2020)
The Difference in Average DMF-T in Communities that Consume Refillable Bottled Drinking Water and Precipitated River Water. The average DMF-T index for Indonesia is 4.6 with a value of D-T component is 1.6, M-T component is 2.9, and an F-T component is 0.08. It means, tooth decay in Indonesian people is 460 teeth per 100 people (Riskesdas., 2013). The DMF-T index for Provinsi Kalimantan Selatan is 6.83, with a value of D-T component is 1.31, M-T component is 5.52, and F-T component is 0.12. It means, the average of tooth decay per person (severity of teeth per person) is 6.83 teeth or 7 teeth (Riskesdas., 2007). This study aimed to determine the difference of DMF-T average in people who consumed refillable bottled water and people who consumed river water treated by deposited, in Desa Samuda, Kecamatan Daha Selatan, Kabupaten Hulu Sungai Selatan, Provinsi Kalimantan Selatan. This research was an analytical survey with cross sectional approach. The sample of this research was all of the people in Desa Samuda, Kecamatan Daha Selatan, Kabupaten Hulu Sungai Selatan, as 110 participants. The independent variable was refilled bottled drinking water and deposited river water. The results showed that the DMF-T average in people who consumed refillable bottled water was 6.42 and the DMF-T average in people who consumed deposited river water was 8.20. Based on the result of the Independent T-Test, the value of sig (2-tailed) p = 0.004 was less than α = 0.05; (p